The awareness of credit card holder towards the knowledge and skill of personal finance / Nurul Alyssa Abdul Rais - Abdul Rais, Nurul Alyssa (2011)
Personal finance is a tool for achieve financial and management money decision. Credit card bankruptcies in Malaysia trebled from 2009 to 2010 thus most of credit card holder experience bad outstanding balance and blacklisted. In response to this, the project paper aims to investigate the level of general financial awareness among credit card holders and determine the relationship between credit card holder awareness and personal finance knowledge and skill. The three research questions addressed are: What is the level of credit card holder’s awareness towards personal finance? Is there any relationship between credit card holder’s awareness and personal finance knowledge? And is there any relationship between credit card holder’s awareness and personal finance skills? A survey method was employed using a sample of 100 respondents around Selangor area that have a credit card. The study also develops normality test, reliable scales, frequency statistic, correlation and regression. The findings of the study revealed that the level of awareness and relationship between dependent and independent variables. The results found that the level of credit card holder awareness is moderate and there is strong relationship. By identifying the specific areas where personal finance awareness may be lacking, the project paper may give recommendation to design financial education programme to educate the cardholder to achieve greater financial freedom.